DESCRIPTION OF BRAINSTEM AUDITORY EVOKED RESPONSES (AIR AND BONE CONDUCTION) IN CHILDREN WITH NORMAL HEARING - A. V. Pashkov; T. A. Polunina; S. A. Kosacheva (Union of pediatricians of Russia, 2014)
Diagnosis of hearing level in small children with conductive hearing loss associated with congenital craniofacial abnormalities, particularly with agenesis of external ear and external auditory meatus is a pressing issue. Conventional methods of assessing hearing in the first years of life, i. e. registration of brainstem auditory evoked responses to acoustic stimuli in the event of air conduction, does not give an indication of the auditory analyzer's condition due to potential conductive hearing loss in these patients. This study was aimed at assessing potential of diagnosing the auditory analyzer's function with registering brainstem auditory evoked responses (BAERs) to acoustic stimuli transmitted by means of a bone vibrator. The study involved 17 children aged 3-10 years with normal hearing. We compared parameters of registering brainstem auditory evoked responses (peak V) depending on the type of stimulus transmission (air/bone) in children with normal hearing. The data on thresholds of the BAERs registered to acoustic stimuli in the event of air and bone conduction obtained in this study are comparable; hearing thresholds in the event of acoustic stimulation by means of a bone vibrator correlates with the results of the BAERs registered to the stimuli transmitted by means of air conduction earphones (r = 0.9). High correlation of thresholds of BAERs to the stimuli transmitted by means of a bone vibrator with thresholds of BAERs registered when air conduction earphones were used helps to assess auditory analyzer's condition in patients with any form of conductive hearing loss.